Investigation of the physical, optical, and photocatalytic properties of CeO2/Fe-doped InVO4 composite. (December 2017) - Chaison, Jindaporn; Wetchakun, Khatcharin; Wetchakun, Natda
Abstract: The CeO2 /Fe-doped InVO4 composites with various Fe concentrations (0.5, 1.0, 2.0, 5.0 and 6.0 mol%) was synthesized by homogeneous precipitation and hydrothermal methods. The as-synthesized samples were characterized by powder X-ray diffraction (XRD), Brunauer Emmett and Teller (BET)-specific surface area, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), and UV–visible diffuse reflectance spectroscopy (DRS). Fe-doping into InVO4 crystal induces the distortion of the crystalline structure, the transformation of InVO4 morphology, and the new energy subband level generation of Fe between the CB and VB edge of InVO4 . The electron excitation from the VB to Fe orbitals results in the decreased band gap and the extended absorption of visible-light, and thus enhances its photocatalytic performance. Visible-light-driven photocatalytic degradation of Rhodamine B (RhB) dye in water was used to evaluate the photocatalytic performance of CeO2 /Fe-doped InVO4 composites. The results revealed that there is an optimum Fe (5.0 mol %) doping level. The composite with the optimum doping level obtains high photocatalytic activity of CeO2 /Fe-doped InVO4 composite compared to pure CeO2 and pure InVO4 host. The increase of photocatalytic activity of CeO2 /Fe-doped InVO4 composite was ascribed to the surface area, crystal defect, and band gap energy. Moreover, the photocatalytic enhancement is also because iron ions act as a trapping site, which results in the higher separation efficiency of photogenerated electrons and holes pairs in the CeO2 /InVO4 composite. The evaluation of radical scavengers confirmed that hydroxyl radical was the main active species during the photodegradation of RhB. These synergistic effects are responsible for the enhanced photocatalytic activity of CeO2 /Fe-doped InVO4 composite. Furthermore, the possible enhanced photocatalytic mechanism of the CeO2 /Fe-doped InVO4 composite was also proposed based on the calculation of band position. Graphical abstract: Highlights: Novel CeO2 /Fe-doped InVO4 composites were synthesized via chemical methods. Enhanced visible-light photocatalytic activities were evaluated for RhB degradation. CeO2 /Fe-doped InVO4 composite promotes charge separation/transfer property. Visible-light photocatalytic mechanism of CeO2 /Fe-doped InVO4 was discussed.